Konsep Auliya Dalam Al-Maidah Ayat 51 dan 57: Pendekatan Integratif-Interkonektif M. Amin Abdullah - Acim, Subhan Abdullah; Sugiarto, Fitrah; Hidayatulloh , Shopian (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2023)
Aksi 212 is a response to Ahok's statement regarding the concept of auliya towards Surat Al-Maidah verse 51. This response gave rise to an understanding of truth claims, namely an understanding that wants to absolute its thoughts regarding the Al-Qur'an. Understanding truth claims also raises an attitude of disbelief towards groups that are different from them. Specifically, this study wants to ask three questions, including 1) What are the views of the mufassir regarding the concept of auliya' in Surat Al-Maidah verse 51 and 57?  2) What is the background to the emergence of the discussion regarding the concept of auliya in Surat Al-Maidah verse 51 and 57? 3) How is the effectiveness of the integrative-interconnective approach in understanding Surat Al-Maidah verse 51 and 57 in the industrial era 4.0? To answer these questions, this research uses an integrative-interconnective approach, which provides a portion of the balance between Islamic sciences and exact sciences. The results in this study are 1) From the views of the mufassir above, it can be concluded, said Auliya in Surat Al-Maidah verse 51 and 57 shows more in the context of social interaction, so this verse speaks of a Muslim being cautious about entering into an agreement with non-Muslims because of his attitude that often violates agreements. 2) Through the analysis of asbabun nuzul, it can be concluded that the main message from Surat Al-Maidah verse 51 and 57 is a prohibition for any group or community to violate agreements or agreements that have been agreed upon. 3) Standardization of leadership is not based on religion, but values that exist in religion, social, culture, and others. The most important thing is to explore the essential values of leadership in the Qur'an, rather than being preoccupied with issues of identity. Keywords : Auliya, Integration-Interconnection, M. Amin Abdullah, Tafsir